2019
DOI: 10.1371/journal.pone.0224579
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of primary postpartum hemorrhage: An implication for designing effective intervention at selected hospitals, Southern Ethiopia

Abstract: BackgroundPrimary postpartum hemorrhage is the leading cause of maternal mortality worldwide. Ethiopia has made significant progress in maternal health care services. Despite this, primary postpartum hemorrhage continues to remain the leading cause of maternal mortality in Ethiopia. This study aimed to assess the prevalence and predictors of primary postpartum hemorrhage among mothers who gave birth at selected hospitals in the Southern Ethiopia.MethodsAn institution-based cross-sectional study was employed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 24 publications
(49 reference statements)
9
73
1
4
Order By: Relevance
“…This is in contrast with the findings of Natakorn et al, [37] Sittiparn and Siwadune [8] confirming that advanced women age (greater than 35 years) is a PPH risk factor. Our findings also are in accord with a study conducted in Ethiopia to describe the prevalence and predictors of primary PPH, [58] which suggested that maternal age of or greater than 35, complicated labor, PPH in previous pregnancies and deliveries performed with aid of instruments were also predictors of primary PPH. Durmaz and Komurcu [57] recommended that midwives, nurses and obstetricians should cautiously monitor women who present with specific characteristics that are significantly associated with PPH during the antepartum, intrapartum and post-partum period.…”
Section: Risk Factors Associated With Pphsupporting
confidence: 91%
“…This is in contrast with the findings of Natakorn et al, [37] Sittiparn and Siwadune [8] confirming that advanced women age (greater than 35 years) is a PPH risk factor. Our findings also are in accord with a study conducted in Ethiopia to describe the prevalence and predictors of primary PPH, [58] which suggested that maternal age of or greater than 35, complicated labor, PPH in previous pregnancies and deliveries performed with aid of instruments were also predictors of primary PPH. Durmaz and Komurcu [57] recommended that midwives, nurses and obstetricians should cautiously monitor women who present with specific characteristics that are significantly associated with PPH during the antepartum, intrapartum and post-partum period.…”
Section: Risk Factors Associated With Pphsupporting
confidence: 91%
“…Indicators of excess weight in terms of BMI or pregnancy Weight gain especially coupled to older pregnancy age increase preterm risk [16,17]. It is noteworthy that besides the social status, the high incidence of hemorrhage in this group of women, reaching 29% that is higher even in comparison to some countries of lower national income [18] led to the highest adjusted odds ratio for PTB of 6.88 to 10.24 (95% interval).…”
Section: Discussionmentioning
confidence: 98%
“…The definition of primary postpartum haemorrhage (PPH) is that of blood loss from the genital tract of ≥500 mL or more following a normal vaginal delivery or ≥1,000 mL or more following a cesarean section within 24 hours of delivery as evidenced by a rise in the pulse rate, and falling blood pressure [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%